Comparative assessment on the effect of long vis-à-vis short-term progesterone priming on reproductive attributes in silent estrus goats - BALAGANUR, KRISHNAPPA; MISRA, S S; MAHLA, AJIT SINGH; DE, KALYAN; KUMAR, RAJIV; SANKHYAN, S K; GOPI, MARAPPAN (The Indian Journal of Animal Sciences, 2024)
Silent estrus results in spread-out kidding and extended inter-kidding interval in goats. Progesterone (P4) priming for 12-14 days could be one of the approaches for estrus induction with optimum fertility. The present work was carried to comparatively assess the duration of P4 priming on estrus and fertility in silent estrus goats. Sirohi does (n=18) with a history of anestrus and high basal P4 in paired samples were equally divided into three groups. Does in P-0 d group received 200 IU of equine chorionic gonadotropin by intramuscular route. Does in group second and third were subjected to per-vaginal P4 sponges for 7 (P-7 d) and 14 (P-14 d) days, respectively and were given 200 IU equine chorionic gonadotropin following sponge withdrawal. Estrus was monitored for 72 h at 12 h intervals using teaser buck to record estrus per cent, induction time and duration. Estrus induction was highest in P-14 d (6/6) than P-0 d and P-7 d (4/6 and 5/6), respectively. Estrus induction time was shorter in P-7 d and P-14 d than P-0 d. The estrus duration was shortest in P-14 d group. The conception and pregnancy rate did not differ significantly among the groups, though all the does in P-14 d conceived. The fertility was non-significantly higher in P-14 d (6/6) and P-7 d group (5/5) than P-0 d (3/4). It could be concluded that P4 priming for 7-14 days in silent estrus does results in improved reproductive performances.